Chemotherapy-induced CAF-associated stromal remodeling in a humanized stroma pancreatic ductal adenocarcinoma organoid xenograft model: a comparison between GP and GS - Kaoru Furihata; Waka Iwashita; Atsushi Kurabayashi; Mutsuo Furihata; Kazushige Uchida; Keisuke Taniuchi (Human Cell, 2026)
Pancreatic ductal adenocarcinoma features a dense, desmoplastic tumor microenvironment (TME) dominated by cancer-associated fibroblasts (CAFs). While gemcitabine plus nab-paclitaxel (approximated as gemcitabine plus paclitaxel [GP]) and gemcitabine plus S-1 (GS) are standard regimens with distinct clinical indications, their specific effects on tumor suppression and CAF-associated stromal remodeling remain unclear. Using a humanized, three-dimensional (3D) S2-013 organoid xenograft model integrating human mesenchymal stem cells (MSCs) and human endothelial cells, we investigated the histopathological and immunohistochemical alterations induced by GP and GS. We quantitatively evaluated tumor parenchymal growth using cytokeratin 19 (CK19) and CAF-associated marker profiles, including α-smooth muscle actin (αSMA), fibroblast activation protein (FAP), platelet-derived growth factor receptors (PDGFR), and interleukin-6 (IL-6). Both regimens clearly suppressed tumor growth, but only GP significantly reduced parenchymal tumor growth compared with untreated controls. Notably, the treatments selectively remodeled the peritumoral stroma in the humanized xenograft model: PDGFR-expressing CAF-like cells were significantly reduced in the GP group, whereas FAP-expressing CAF-like cells and IL-6-expressing stromal cells were significantly decreased in the GS group. αSMA expression showed a general decreasing trend in both therapeutic arms. In summary, GP and GS chemotherapies induced distinct, measurable humanized TME remodeling modalities beyond direct cytotoxicity. By successfully recapitulating drug–stroma interactions and suggesting the human MSC origin of the peritumoral CAFs, this study demonstrates the robustness of our organoid xenograft model as a powerful preclinical screening platform for evaluating and predicting the efficacy of novel stroma-targeted and immunomodulatory investigative compounds.